Mineralized collagen coated licochalcone nanocrystal as well as preparation method and application thereof
By coating the surface of glycyrrhizin chalcone nanocrystals with a mineralized collagen layer and utilizing the biomimetic composite of hydroxyapatite and collagen, the problems of dispersion stability and bioavailability of glycyrrhizin chalcone in cosmetics are solved, achieving high solubility and stability of the nanocrystals, and possessing intelligent release and whitening and mole removal effects.
Patent Information
- Application Number
- CN202511062747.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2025-10-31
AI Technical Summary
Glycyrrhizin has poor water solubility, which limits its dispersion stability and bioavailability in cosmetics. Nanocrystalline suspensions are prone to aggregation or crystal growth during long-term storage or use. Existing nanocarriers have low loading efficiency and cannot effectively control drug release.
By employing nanoshell self-locking technology, a mineralized collagen layer is coated onto the surface of glycyrrhizin chalcone nanocrystals. A stable encapsulation structure is formed by the biomimetic composite of hydroxyapatite and collagen. Combined with charge modification and in-situ mineralization reaction, the stability and sustained-release effect of the nanocrystals are improved.
It achieves high solubility, high bioavailability and long-term stability of glycyrrhizin chalcone nanocrystals, enabling intelligent release in the skin's slightly acidic environment, enhancing the anti-inflammatory and soothing effects of cosmetics, and possessing the functions of removing moles, freckles and whitening.
Smart Images

Figure CN120859867A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of cosmetic technology, specifically relating to a mineralized collagen-encapsulated glycyrrhizin chalcone nanocrystals, its preparation method, and its application. Background Technology
[0002] Glycyrrhizin chalcone is a flavonoid compound extracted from the root of licorice. It possesses strong anti-inflammatory and antioxidant properties, and is therefore widely used in cosmetic formulations. However, glycyrrhizin chalcone has poor water solubility, exhibiting good solubility only in a few organic solvents such as methanol, ethanol, and propylene glycol. Furthermore, its crystalline nature leads to poor dispersion stability and limited bioavailability in its applications.
[0003] To effectively improve the solubility and bioavailability of poorly soluble drugs, nanocrystal technology has been introduced. Nanocrystal technology significantly increases the specific surface area of drugs by forming them into nanocrystals, thereby improving solubility and bioavailability. However, improving the stability of nanocrystals presents significant challenges. In suspensions of strongly crystalline drug nanocrystals, the difference in solubility between particles of different sizes leads to Austronesian ripening, where larger particles gradually grow by consuming smaller particles, thus reducing the stability of the suspension. Although some researchers have attempted to load nanomedicines using nanocarriers, the loading efficiency of nanocarriers for drugs still needs improvement, and they cannot effectively limit drug dissolution and nanocrystal growth.
[0004] Collagen is a biomaterial with good biocompatibility, biodegradability, and low immunogenicity. When applied to cosmetics, it can play a role in moisturizing and locking in moisture. Numerous studies have shown that collagen and its hydrolysates can improve skin cell activity and also have the ability to repair damaged skin. However, nanocrystalline modified layers formed solely from collagen deposition suffer from insufficient stability.
[0005] Hydroxyapatite exhibits excellent biocompatibility, binding tightly to surrounding tissues without causing rejection or exclusion reactions. In patent documents CN110115772B and CN11558041A, hydroxyapatite has been used to encapsulate drugs, significantly improving the stability of drug particles. However, similarly, using hydroxyapatite alone for encapsulation also suffers from low strength and easy structural damage. Mineralized collagen can biomimeticly combine hydroxyapatite and collagen at the molecular level, forming a system with high homogeneity, high porosity, and good biocompatibility. However, mineralized collagen is typically used for bone tissue repair, and there is currently no research on its use for encapsulating crystalline drugs for application in cosmetics.
[0006] In summary, in existing technologies, glycyrrhizin chalcone, as a natural compound with various biological activities, is limited in its application due to its low water solubility and low bioavailability. Although it can be prepared into nanocrystals through antisolvent precipitation, thereby significantly increasing its specific surface area and improving solubility and bioavailability, the nanocrystal dispersions are prone to aggregation or crystal growth during long-term storage or use, resulting in poor stability and limiting its practical application. Therefore, providing a mineralized collagen-encapsulated glycyrrhizin chalcone nanocrystal with high solubility, high bioavailability, and high stability is of great significance for expanding the application range of glycyrrhizin chalcone in the cosmetic field. Summary of the Invention
[0007] To address the problems existing in the prior art, this invention innovatively proposes a stabilization strategy for glycyrrhizin nanocrystals encapsulated with mineralized collagen. By employing NanoShellock technology, a mineralized collagen layer is encapsulated on the surface of the glycyrrhizin nanocrystals, thereby improving the long-term stability and controllability of the sustained-release effect.
[0008] In a first aspect of the present invention, a mineralized collagen-encapsulated glycyrrhizin nanocrystals is provided, wherein the mineralizing material in the mineralized collagen is hydroxyapatite, the content of the mineralized collagen is 15-60 wt%, the content of the hydroxyapatite is 1-20 wt%, and the total weight of the mineralized collagen-encapsulated glycyrrhizin nanocrystals is used as a basis.
[0009] Specifically, the content of the mineralized collagen is 15, 20, 25, 30, 35, 40, 45, 50, 55, or 60 wt%. The content of the hydroxyapatite is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20 wt%.
[0010] Furthermore, the collagen is animal collagen and / or recombinant collagen.
[0011] Furthermore, the hydroxyapatite is obtained through an in-situ mineralization reaction using a calcium ion source and a phosphate ion source.
[0012] Further, the calcium ion source is a calcium salt, selected from one or more of calcium chloride, calcium nitrate, calcium carbonate, and calcium citrate. In some embodiments of the present invention, the calcium ion source is calcium chloride.
[0013] Further, the phosphate ion source is phosphoric acid or a phosphate, wherein the phosphate is selected from one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, potassium phosphate, calcium dihydrogen phosphate, calcium phosphate, sodium phosphate, and diammonium phosphate. In some embodiments of the present invention, the phosphate ion source is sodium dihydrogen phosphate and disodium hydrogen phosphate.
[0014] A second aspect of the present invention provides a method for preparing mineralized collagen-encapsulated glycyrrhizin chalcone nanocrystals, the method comprising:
[0015] 1) Preparation of charge-modified glycyrrhizin chalcone nanocrystal suspension;
[0016] 2) Adjust the pH of the crude suspension to 5.5-6.5 and add it to the collagen aqueous solution to form a collagen coating layer on the nanocrystals;
[0017] 3) The product obtained in step 2) is mixed with calcium ion source and phosphate ion source and mineralized in situ to obtain mineralized collagen-encapsulated glycyrrhizin nanocrystals.
[0018] This invention achieves this by separately controlling the charge on glycyrrhizin and collagen, allowing collagen molecules to uniformly coat the surface of glycyrrhizin nanocrystals through electrostatic binding, forming a collagen shell, and then performing in-situ mineralization to construct a stable encapsulation structure of mineralized collagen, ultimately obtaining mineralized collagen-encapsulated glycyrrhizin nanocrystals with excellent dispersibility and long-term stability.
[0019] Furthermore, the reagents used for charge modification include charge stabilizers and non-charge stabilizers.
[0020] Further, step 1) includes: adding an oil phase formed by glycyrrhizin, a charge stabilizer and a good solvent to an aqueous phase formed by a non-charge stabilizer and water to obtain a charge-modified glycyrrhizin nanocrystal suspension.
[0021] Further, the charge stabilizer is selected from one or more of oleic acid, arachidic acid, palmitic acid, stearic acid, lauric acid, myristic acid, palmitoleic acid, gallic acid, lecithin, and soybean lecithin, preferably one or more of arachidic acid, palmitic acid, stearic acid, lauric acid, and myristic acid. In some embodiments of the present invention, the charge stabilizer is palmitic acid.
[0022] Further, the non-charge stabilizer is selected from one or more of Tween (e.g., Tween 20, Tween 40, Tween 60, Tween 80), poloxamer (e.g., poloxamer 188, poloxamer 407), polyethylene glycol (e.g., polyethylene glycol 200, polyethylene glycol 600, polyethylene glycol 6000), polyvinylpyrrolidone, polyvinyl alcohol, polyoxyethylene fatty alcohol ether, polyoxyethylene fatty acid ester, polyoxyethylene glycerol ester, hydroxyethyl cellulose, and hydroxypropyl methylcellulose, preferably one or more of Tween 80, poloxamer 188, poloxamer 407, polyethylene glycol, polyoxyethylene fatty alcohol ether, polyoxyethylene fatty acid ester, and polyoxyethylene glycerol ester. In some embodiments of the present invention, the non-charge stabilizer is Tween 80.
[0023] Further, the good solvent is selected from one or more of methanol, ethanol, diethyl ether, isopropanol, acetonitrile, tetrahydrofuran, acetone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone, preferably one or more of methanol, ethanol, and isopropanol. In some embodiments of the present invention, the good solvent is ethanol.
[0024] Further, in step 1), the glycyrrhizin chalcone, after being dissolved in a good solvent, has a mass-volume percentage concentration of 0.1-10% (w / v%, g / mL), specifically such as 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, or 10%, preferably 4-6%. In some embodiments of the present invention, the glycyrrhizin chalcone, after being dissolved in a good solvent, has a mass-volume percentage concentration of 5%.
[0025] Further, in step 1), the mass-volume percentage concentration of the charge stabilizer dissolved in a good solvent is 0.01-5% (w / v%, g / mL), specifically such as 0.01, 0.05, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.8, 1, 1.2, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5%, preferably 0.05-0.2%. In some embodiments of the present invention, the mass-volume percentage concentration of the charge stabilizer dissolved in a good solvent is 0.1%.
[0026] Further, in step 1), the mass-volume percentage concentration of the non-charge stabilizer dissolved in water is 0.1-10% (w / v%, g / mL), specifically such as 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10%, preferably 4-6%. In some embodiments of the present invention, the mass-volume percentage concentration of the non-charge stabilizer dissolved in water is 5%.
[0027] Further, in step 1), the rate at which the oil phase is added to the aqueous phase is 0.1-1 mL / min, specifically 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1 mL / min, preferably 0.3-0.4 mL / min. In some embodiments of the present invention, the rate at which the oil phase is added to the aqueous phase is 0.3 mL / min.
[0028] Further, in step 1), the oil phase is added to the aqueous phase, and stirring and ultrasonication are performed simultaneously; the ultrasonic power is 500-5000W, specifically 500, 600, 700, 800, 900, 1000, 5000W, and in some embodiments of the present invention, the ultrasonic power is 600W.
[0029] Further, in step 2), the reagent used to adjust the pH value is an acidic solution selected from one or more of formic acid, acetic acid, propionic acid, butyric acid, citric acid, oxalic acid, succinic acid, tartaric acid, and malic acid. In some embodiments of the present invention, the acidic solution used is acetic acid.
[0030] Furthermore, the collagen is derived from animal collagen and / or recombinant collagen.
[0031] Further, in step 2), the mass ratio of the nanocrystals to collagen is 1:(0.1-1.5), specifically 1:0.1, 1:0.5, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, and 1:1.5. In some embodiments of the present invention, the mass ratio of the nanocrystals to collagen is 1:1.
[0032] Optionally, step 2) may include the following step before adjusting the pH: rotary evaporating the crude suspension obtained in step 1).
[0033] Further, in step 2), the reaction temperature is room temperature (20-30℃, such as 20, 22, 25, 27, 30℃); the stirring speed is 500-1000 rpm (such as 500, 600, 700, 800, 900, 1000 rpm).
[0034] Further, step 3) includes: mixing the collagen-encapsulated glycyrrhizin nanocrystals obtained in step 2) with a buffer solution containing calcium and phosphate ions with pH adjusted to a weakly alkaline state, and performing in-situ mineralization to obtain mineralized collagen-encapsulated glycyrrhizin nanocrystals.
[0035] Further, in step 3), the calcium ion source is selected from one or more of calcium chloride, calcium carbonate, calcium phosphate, calcium nitrate, and calcium citrate. In some embodiments of the present invention, the calcium ion source is calcium chloride.
[0036] Further, in step 3), the phosphate ion source is selected from one or more of phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, potassium phosphate, calcium dihydrogen phosphate, calcium phosphate, sodium phosphate, and diammonium phosphate. In some embodiments of the present invention, the phosphate ion source is sodium dihydrogen phosphate and disodium hydrogen phosphate.
[0037] Further, in step 3), the molar concentration of calcium ions in the buffer solution is 0.01-0.5 mol / L, specifically such as 0.01, 0.03, 0.05, 0.08, 0.1, 0.12, 0.15, 0.2, 0.3, 0.4, or 0.5, preferably 0.03-0.2 mol / L. In some embodiments of the present invention, the molar concentration of calcium ions in the buffer solution is 0.12 mol / L or 0.03 mol / L.
[0038] Further, in step 3), the molar concentration of phosphate ions in the buffer solution is 0.01-0.5 mol / L, specifically such as 0.01, 0.04, 0.05, 0.08, 0.1, 0.12, 0.15, 0.2, 0.3, 0.4, or 0.5, preferably 0.04-0.2 mol / L. In some embodiments of the present invention, the molar concentration of phosphate ions in the buffer solution is 0.08 mol / L or 0.04 mol / L.
[0039] Further, in step 3), the molar ratio of calcium ions to phosphate ions in the buffer solution is (0.5-5):1, specifically such as 0.5:1, 0.75:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, preferably (0.75-1.5):1. In some embodiments of the present invention, the molar ratio of calcium ions to phosphate ions in the buffer solution is 1.5:1 or 0.75:1.
[0040] Further, in step 3), the weakly alkaline pH value is 7-8, specifically such as 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, or 8.0, preferably 7.2-7.8. In some embodiments of the present invention, the weakly alkaline pH value is 7.4.
[0041] Further, in step 3), the reagent used to adjust the pH value is an alkaline reagent, selected from one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate, potassium bicarbonate, sodium carbonate, potassium carbonate, disodium hydrogen phosphate, and dipotassium hydrogen phosphate. In some embodiments of the present invention, the alkaline reagent is sodium hydroxide.
[0042] Further, in step 3), the temperature of the in-situ mineralization reaction is 15-40°C, specifically 15, 18, 20, 22, 25, 28, 30, 32, 35, 37, or 40°C, preferably 15-37°C. In some embodiments of the present invention, the temperature of the in-situ mineralization reaction is 35°C or 20°C.
[0043] Further, in step 3), the in-situ mineralization reaction takes 6-72 hours, specifically 6, 12, 18, 24, 30, 36, 42, 48, 54, 60, 66, or 72 hours. In some embodiments of the present invention, the in-situ mineralization reaction takes 24 hours or 60 hours.
[0044] Furthermore, in step 3), after the in-situ mineralization reaction is completed, the step of centrifugation and collection of the precipitate is also included; even further, step 3) may also include the steps of dialysis (e.g., dialysis with purified water using a dialysis bag to remove soluble salts) and drying (e.g., freeze-drying to remove excess moisture) of the precipitate.
[0045] Further, the glycyrrhizin is selected from one or more of glycyrrhizin A, glycyrrhizin B, glycyrrhizin C, glycyrrhizin D, and glycyrrhizin E. In some embodiments of the present invention, the glycyrrhizin is glycyrrhizin A.
[0046] Furthermore, the nanocrystals can be used to prepare nanocrystalline formulations, nanoparticle formulations, nanosuspensions, or nanoemulsions. In some embodiments of the present invention, the nanocrystals are used to prepare nanocrystalline formulations.
[0047] In a third aspect of the invention, an emulsion composition is provided, the emulsion composition comprising mineralized collagen-encapsulated glycyrrhizin nanocrystals of the first aspect or mineralized collagen-encapsulated glycyrrhizin nanocrystals prepared in the second aspect, an emulsifier, and a thickener.
[0048] Furthermore, the emulsion composition also contains other active ingredients.
[0049] Furthermore, the emulsifier includes, but is not limited to, one or both of hydrogenated lecithin and polydimethylsiloxane.
[0050] Furthermore, the thickener includes, but is not limited to, one or more of carboxymethyl cellulose, xanthan gum, and sodium hyaluronate.
[0051] Furthermore, the other active ingredients include, but are not limited to, one or both of carnosine and ergothioneine.
[0052] In a fourth aspect of the invention, the application of mineralized collagen-encapsulated glycyrrhizin nanocrystals in the preparation of cosmetics is provided.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] (1) This invention modifies the charge of glycyrrhizin chalcone, enabling the weakly charged glycyrrhizin chalcone component to attract collagen with opposite charges to its surface via electrostatic bonding, forming a collagen shell. The collagen shell enhances the stability of glycyrrhizin chalcone, improves its bioactivity, and strengthens its moisturizing properties. Subsequently, through in-situ mineralization, a mineralized collagen layer is formed. This improves the structural stability of the collagen layer, making the glycyrrhizin chalcone nanocrystals exhibit higher stability and meeting the requirements for long-term storage. Furthermore, hydroxyapatite has good pH responsiveness, which allows it to control the release of glycyrrhizin chalcone in a slightly acidic environment close to that of the skin, achieving efficient dissolution of glycyrrhizin chalcone when used in cosmetics, thereby exerting a good anti-inflammatory and soothing effect.
[0055] (2) This invention obtains mineralized collagen-encapsulated glycyrrhizin nanocrystals through charge modification, collagen deposition, and in-situ mineralization. Compared to collagen-hydroxyapatite complexes formed by simple physical blending, which suffer from poor uniformity and difficulty in effectively encapsulating the nanocrystal drugs, the method of this invention can produce nanocrystals with small particle size, high specific surface area, high drug loading capacity, and high biocompatibility. Simultaneously, it greatly improves the stability of glycyrrhizin nanocrystals. Combining collagen with hydroxyapatite not only improves the stability of the entire system but also endows the system with intelligent release properties under the weakly acidic conditions of the skin. Furthermore, some studies have shown that the combination of the two has the effects of removing moles, freckles, reducing pigmentation, and whitening. Therefore, using the form of mineralized collagen-encapsulated nanocrystals in this invention can better exert the effects of anti-melanin deposition and whitening, showing very good clinical application prospects in the field of cosmetics. Attached Figure Description
[0056] Figure 1 Macroscopic photographs (a) and microscopic observations ((b) Comparative Example 1, (c) Comparative Example 2 and (d) Example 1) of the purified water dispersion of Comparative Example 1, Comparative Example 2 and Example 1, with a scale bar of 50 μm.
[0057] Figure 2 Macroscopic photographs (a) and microscopic observations ((b) Comparative Example 1, (c) Comparative Example 2 and (d) Example 1) after 15 days of storage for Comparative Example 1, Comparative Example 2 and Example 1, with a scale bar of 50 μm.
[0058] Figure 3 XRD test results of Examples 1-4 and Comparative Example 2.
[0059] Figure 4 Thermogravimetric test results of Comparative Example 2 and Example 1:
[0060] Figure 5Figure 1 shows the results of glycyrrhizin A release tests in Examples 1-4 and Comparative Examples 1-2 at pH 7 and pH 5 ((a) pH 7, (b) pH 5).
[0061] Figure 6 Transdermal test results of Examples 1-4 and Comparative Examples 1-2.
[0062] Figure 7 Anti-inflammatory effects of different concentrations of Example 1 and Comparative Examples 1 and 2 are shown in the figure. Detailed Implementation
[0063] Unless otherwise defined, all scientific and technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.
[0064] All publications, patents, and published patent specifications cited in this article are incorporated herein in their entirety through citation.
[0065] All raw materials and reagents used in this article are commercially available.
[0066] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0067] Example 1:
[0068] A mineralized collagen-encapsulated glycyrrhizin chalcone A nanocrystal formulation, the preparation of which mainly includes the following steps:
[0069] 1) Weigh 1.00 g of glycyrrhizin chalcone A and 0.02 g of palmitic acid, add 20 mL of ethanol, shake at room temperature to dissolve completely, and obtain an oil phase solution; weigh 2.00 g of Tween 80, add 40 mL of purified water, heat and stir at 60 °C for 10 min to dissolve completely, and obtain an aqueous phase solution; add the oil phase solution dropwise to the aqueous phase solution at a rate of 10 mL / 30 min, while simultaneously stirring and sonicating at a sonication power of 600 W, to obtain a crude suspension of palmitic acid-modified glycyrrhizin chalcone A nanocrystals;
[0070] 2) The crude suspension obtained in step 1) was subjected to vacuum distillation at 80°C for 3 hours to remove most of the drug solvent (ethanol). After cooling to room temperature, a small amount of acetic acid was added to adjust the solution to a weakly acidic pH of 6. Then, under high-speed stirring at 700 rpm, 300 ml of collagen aqueous solution (1.00 g of animal-derived type I collagen lyophilized powder was dissolved in 300 ml of purified water, and the mass ratio of collagen to glycyrrhizin A nanocrystals was 1:1) was added to obtain a collagen-encapsulated glycyrrhizin A nanocrystal suspension.
[0071] 3) Prepare calcium ion source and phosphate ion source solutions (dissolve 5.33g of anhydrous calcium chloride, 1.69g of sodium dihydrogen phosphate powder and 2.54g of disodium hydrogen phosphate powder in 400ml of purified water, wherein the molar ratio of calcium ions to phosphate ions is 1.5:1). Adjust the pH of the solution to a weakly alkaline 7.4 with sodium hydroxide to prepare a buffer solution for calcium ion source and phosphate ion source. Then mix the collagen-encapsulated glycyrrhizin A nanocrystal suspension obtained in step 2) with the buffer solution, incubate at 35℃ with shaking for 24h, dialyze with purified water in a 1000D dialysis bag to remove soluble salts, freeze-dry to remove excess water, and obtain mineralized collagen-encapsulated glycyrrhizin A nanocrystals.
[0072] Example 2:
[0073] Except for replacing “animal-derived type I collagen freeze-dried powder” in Example 1 with “recombinant collagen”, all other steps are the same as in Example 1.
[0074] Example 3:
[0075] Except for replacing “1.00g of animal-derived type I collagen freeze-dried powder” with “0.50g of animal-derived type I collagen freeze-dried powder” in Example 1, all other steps are the same as in Example 1.
[0076] Example 4:
[0077] Except for replacing "5.33g anhydrous calcium chloride, 1.69g sodium dihydrogen phosphate powder and 2.54g disodium hydrogen phosphate powder" in Example 1 with "1.33g anhydrous calcium chloride, 0.85g sodium dihydrogen phosphate powder and 1.27g disodium hydrogen phosphate powder", and replacing "35°C shaking incubation for 24h" with "20°C shaking incubation for 60h", all other steps are the same as in Example 1.
[0078] Comparative Example 1:
[0079] The palmitic acid-modified glycyrrhizin A nanocrystals crude suspension obtained in step 1) of Example 1 was subjected to vacuum distillation at 80°C for 3 hours to remove most of the drug solvent (anhydrous ethanol), cooled to room temperature, and freeze-dried to obtain glycyrrhizin A nanocrystals.
[0080] Comparative Example 2:
[0081] The collagen-encapsulated glycyrrhizin A nanocrystal suspension obtained in step 2) of Example 1 was freeze-dried to remove excess water, and then collagen-encapsulated glycyrrhizin A nanocrystals were obtained.
[0082] Performance testing:
[0083] Performance Example 1: Morphology and Stability Testing
[0084] Take 50 mg of each sample from Examples 1-4 and Comparative Examples 1-2, and disperse them thoroughly in 10 ml of purified water. Observe their macroscopic state, and take an appropriate amount of sample to observe their microscopic morphology under an optical microscope. The results are as follows: Figure 1 As shown.
[0085] The samples were then placed in a constant temperature and humidity chamber at 50℃ (75% humidity) for accelerated stability testing. After 15 days, the macroscopic state of each suspension was observed, and the stability of each suspension was determined by observing the changes in the microstructure of the nanocrystals using an optical microscope. The results are as follows: Figure 2 As shown in Table 1, the particle size of each sample before (0D: after solution preparation) and after (15D: after accelerated stability test) was analyzed using a laser particle size analyzer.
[0086] Table 1. Particle size changes of different samples after 0 days and 15 days of storage at 50℃.
[0087] sample 0D(μm) 15D(μm) rate of change Example 1 1.63 1.82 11.7% Example 2 1.58 1.78 12.7% Example 3 0.99 1.27 28.3% Example 4 1.52 1.79 17.8% Comparative Example 1 0.54 / / Comparative Example 2 1.53 3.58 134.0%
[0088] from Figure 1 As can be seen, the nanocrystalline crude suspensions of Example 1 and Comparative Examples 1-2 are all pale yellow liquids, and there is no significant difference in macroscopic state among the groups (see...). Figure 1 (a)); Further microscopic observation shows that uniform glycyrrhizin A nanocrystals can be prepared by the antisolvent method of Comparative Example 1 (see Figure 1 (b) After collagen encapsulation and mineralization, the size of the nanocrystals increased slightly, and a small number of nanocrystals were encapsulated by collagen to form a whole, but overall they still exhibited a uniform particle dispersion (see [link]). Figure 1 (c) Figure 1 (d)).
[0089] As can be seen from Table 1, the nanocrystals of Comparative Example 1 have a size of about 0.54 μm; however, after adding collagen for encapsulation, the overall size of the nanocrystals increases significantly, with the nanocrystals of Comparative Example 2 reaching a particle size of 1.53 μm; further, after in-situ mineralization of the collagen-encapsulated nanocrystals, the size of the encapsulation layer increases further, as shown in Example 1, reaching 1.63 μm, indicating that mineralized collagen encapsulation was effectively achieved on the surface of the nanocrystals.
[0090] After being placed in a constant temperature and humidity chamber at 50℃ for 15 days, from Figure 2 As can be seen, the unencapsulated nanocrystals in Comparative Example 1 aggregated (see...). Figure 2 (a) produced a large number of orange crystals, which precipitated to form a precipitate; the dispersion of Comparative Example 2 was improved compared to Comparative Example 1, but its overall suspension also changed from pale yellow to orange, which also means that glycyrrhizin A formed large-sized crystals; while in Example 1 only a small amount of orange appeared, and the overall color was still pale yellow, indicating that in-situ mineralization on the basis of collagen encapsulation can greatly improve the stability of nanocrystals.
[0091] Furthermore, as can be seen from Table 1, after 15D, the nanocrystal size of Comparative Example 1 could not be measured using a laser particle size analyzer. This is mainly because the unencapsulated nanocrystals in Comparative Example 1 underwent "Austenite ripening," resulting in crystal growth. Microscopic observation revealed that small-sized nanocrystals formed needle-like large-sized crystals (see...). Figure 2 (b) The two-dimensional size of the needle-like crystals far exceeds 200 μm, making particle size testing difficult. In contrast, Comparative Example 2, encapsulated with collagen, showed a significant increase in particle size after storage, reaching 134.0%. This is mainly because when only glycyrrhizin chalcone A is encapsulated with collagen, the collagen swells and redissolves during dispersion, weakening the encapsulation layer. This causes the nanocrystals of Comparative Example 2 to also undergo a certain degree of dissolution and recrystallization, resulting in a significant size increase. Compared to Comparative Example 2, the nanocrystals of Example 1 showed little size change after 15 days of storage, increasing by only 11.7%. This indicates that after encapsulation with collagen, further in-situ mineralization treatment allows the hydroxyapatite component to bind with the collagen, acting similarly to cross-linking points, enhancing the stability of the collagen encapsulation layer. This makes the encapsulated structure less susceptible to damage in solution, resulting in better stability of the nanocrystals.
[0092] Performance Example 2: XRD Test and Thermogravimetric Test
[0093] Take 100 mg of dried samples from Examples 1-4 and Comparative Example 2, press and flatten them, and perform XRD analysis at 10–80° with a scanning speed of 2° / min. The results are as follows. Figure 3 As shown.
[0094] 15–20 mg of dried samples from Examples 1–4 and Comparative Example 2 were taken and subjected to thermogravimetric analysis (TGA) at temperatures ranging from 50–800 °C. The residual amount after the TGA test of Comparative Example 2 was used as a blank subtraction. The difference in residual amounts between Comparative Example 2 and Examples 1–4 was calculated to obtain the hydroxyapatite content in Examples 1–4, and the mineralized collagen content was also calculated. The results are shown in Table 2. Additionally, the TGA curves for Examples 1 and Comparative Example 2 are shown below. Figure 4 As shown.
[0095] Table 2. Content of hydroxyapatite and mineralized collagen in different samples
[0096] sample Example 1 Example 2 Example 3 Example 4 Hydroxyapatite content 12.72% 11.69% 6.49% 4.58% Mineralized collagen content 56.33% 55.75% 37.50% 52.38%
[0097] from Figure 3 As can be seen, compared with Comparative Example 2, Examples 1-4 show obvious characteristic diffraction peaks at 2θ = 32.05°, corresponding to the (211) crystal plane of hydroxyapatite. This also means that in-situ mineralization was successfully carried out on collagen in Examples 1-4. Example 1 has the largest peak intensity. In Example 2, the peak intensity difference was not significant when different types of collagen were used. However, the characteristic peaks of hydroxyapatite decreased significantly when the proportion of collagen was reduced (Example 3) and the proportions of calcium ion source and phosphate ion source were reduced (Example 4), indicating a decrease in the mineralization ratio.
[0098] As can be seen from Table 2, the hydroxyapatite content in Examples 1-2 is basically the same, indicating that changing the type of collagen has little effect on the final mineralization. However, changing the collagen content and the mineralization time, as in Examples 3-4, will affect the final in-situ mineralization ratio to some extent. As the amount of collagen decreases, the mineralization ratio will decrease, and the decrease in the ratio of calcium ion source and phosphate ion source will also reduce the mineralization ratio to some extent.
[0099] In addition, from Figure 4 As can be seen, Comparative Example 2, without mineralization, had a weight loss of 93.79% at 800°C. After in-situ mineralization, Example 1 had a weight loss of 81.07%, meaning that 12.72% of Example 1 was composed of hydroxyapatite. Furthermore, the thermogravimetric curves show that after in-situ mineralization, the slope of the weight loss curve in the range of 230–435°C decreased, which also indicates that the coating layer in Example 1 significantly improved the overall thermal stability of the drug after mineralization.
[0100] Performance Example 3: pH Response Test
[0101] Take 50 mg of each sample from Examples 1-4 and Comparative Examples 1-2, disperse them thoroughly in 10 ml of purified water, and fill them into 1000D dialysis bags. Then, place the dialysis bags into 50 ml centrifuge tubes, adding 20 ml of phosphate solution at pH 5.0 and 7.0 to each tube. At 1 h, 3 h, 5 h, 7 h, 12 h, and 24 h, take 1 ml of the extract from each centrifuge tube, dilute to 50 ml with methanol, and detect the glycyrrhizin A content in the extract using liquid chromatography to illustrate the drug release characteristics of different samples at different pH levels. The test results are as follows: Figure 5 As shown.
[0102] from Figure 5 As can be seen, the unencapsulated Comparative Example 1 exhibited low solubility of glycyrrhizin chalcone A under both acidic (pH=5) and neutral (pH=7) conditions. This may be due to the instability of its nanocrystals, which facilitates crystal growth and limits the drug's saturated solubility. Under neutral conditions (see...), Figure 5 (a)) There was no significant difference in dissolution among Examples 1-4, indicating that the collagen mineralization method of the present invention for encapsulating glycyrrhizin A nanocrystals makes it difficult for the nanocrystals to continue growing, thus improving the stability of the nanocrystals. This conclusion can also be drawn from the storage test of Performance Example 1. In addition, Examples 1-4 under acidic conditions (see Figure 5 (b) There is significant drug dissolution. The introduction of hydroxyapatite makes the encapsulated drug have a certain pH responsiveness. The dissolution of the encapsulation layer and the higher solubility of small-sized nanocrystals enhance the release of glycyrrhizin A under acidic conditions.
[0103] In Comparative Example 2, which only uses collagen encapsulation, glycyrrhizin A showed lower solubility under both acidic and neutral conditions. This is mainly because although the collagen in Comparative Example 2 has a certain encapsulation and stabilizing effect on glycyrrhizin A, the nanocrystals will recrystallize under neutral conditions. Compared with Example 1 with the same drug equivalent, the concentration of the dissolved drug is still lower. However, since Comparative Example 2 did not undergo in-situ mineralization after collagen encapsulation, the slowly swollen and dissolved collagen encapsulation layer in Comparative Example 2 still restricts the dissolution of the drug in acidic solutions. Its dissolution effect is significantly lower than that of Example 1, thus limiting the bioavailability under the conditions of use.
[0104] Performance Example 4: In vitro transdermal test
[0105] Take the skin of Bama fragrant pig, The adipose tissue inside the skin was washed with PBS buffer. The skin was then fixed in the donor and recipient chambers of a Franz diffusion cell, with the stratum corneum facing upwards. The recipient chamber used a 50% ethanol-saline solution as the receiving fluid. During transdermal treatment, the temperature of the receiving cell was set to 32°C, and the stirring speed was 600 rpm. After equilibration for 30 min, 100 mg of each sample from Examples 1-4 and Comparative Examples 1-2 was taken and dispersed in 5 ml of purified water. 200 μl of each sample was applied to one side of the stratum corneum of the pig skin and covered with a coverslip. Samples were automatically collected at 3 h, 6 h, 12 h, and 24 h, and the drug content in the transdermal receiving fluid was detected by liquid chromatography. The results are as follows: Figure 6 As shown.
[0106] from Figure 6 As can be seen, in the early stages of the transdermal test, such as at 3h and 6h, the drug dialysis absorption effects of Examples 1-4 and Comparative Examples 1-2 were quite similar, with relatively small absorption amounts, ranging from 0.17 to 0.26 μg / ml. This indicates that the transdermal absorption effect of nanocrystals is relatively slow, so the difference was not significant in the early stages.
[0107] As the transdermal absorption time increased, the transdermal absorption gradually increased. At 12 hours, the absorption of Examples 1-4 reached 0.99 μg / ml or higher, with Example 1 showing a transdermal absorption of 1.12 μg / ml, significantly higher than Comparative Example 1's 0.72 μg / ml and Comparative Example 2's 0.92 μg / ml. When the test continued for 24 hours, the transdermal absorption increased even more significantly. Example 1 reached 3.98 μg / ml, while Comparative Example 1 only reached 2.53 μg / ml and Comparative Example 2 only reached 3.01 μg / ml. Comparative Example 1 showed the worst dialysis absorption, mainly because glycyrrhizin A nanocrystals are a strong... In Comparative Example 1, the uncoated nanocrystals applied to pigskin rapidly crystallized, limiting subsequent drug penetration. In Comparative Example 2, the nanocrystals were coated with collagen, which enhanced their stability to some extent and increased transdermal absorption to a certain degree. However, this was still significantly inferior to the transdermal absorption in Example 1. This is mainly because, even with collagen coating, the nanocrystals still recrystallized after the collagen coating swelled and dissolved, reducing drug dissolution. Mineralization, on the other hand, significantly increased the sustained release of glycyrrhizin A due to the improved stability of the mineralized collagen coating, thus increasing transdermal absorption on pigskin.
[0108] Performance Example 5: Anti-inflammatory and Soothing Effect Test
[0109] Take 10 mg each of the samples from Example 1 and Comparative Examples 1-2, dissolve them in 5 ml of complete culture medium, and dilute to concentrations 1 (108 μg / ml), 2 (54 μg / ml), and 3 (27 μg / ml) respectively, according to the equivalent of glycyrrhizin A. Collect RAW264.7 cells in the logarithmic growth phase by pipetting, and dilute at 10... 5 Cells were seeded at a density of 500 μL / ml in 24-well plates and incubated at 37°C in a 5% CO2 incubator for 24 h. 500 μL of complete culture medium was added to the blank control group (not induced by lipopolysaccharide (LPS)) and the negative control group (induced by LPS). 500 μL of complete culture medium was added to the positive control group (containing 0.01% dexamethasone), and 500 μL of complete culture medium containing the corresponding concentration of the sample group was added. Cells were incubated at 37°C in a 5% CO2 incubator for another 24 h. After 24 h of culture, the original culture medium was aspirated. 500 μL of complete culture medium was added directly to the blank control group. 500 μL of working solution containing LPS was added directly to the negative control group, sample group, and positive control group. Cells were incubated at 37°C in a 5% CO2 incubator for another 24 h, and the supernatant was collected. After diluting the cell supernatant from each well by 100 times and centrifuging, the supernatant was measured. According to the kit instructions, the absorbance of each well at 450 nm was measured using an ELISA reader. The measured absorbance was substituted into the standard curve to obtain the expression level of the cellular inflammatory factor TNF-α. The arithmetic mean of three TNF-α expression levels (average expression level) was taken as the result. The TNF-α inhibition rate of each group was calculated using the formula shown in equation (1).
[0110]
[0111] In the formula:
[0112] T represents the average TNF-α expression level in the sample group;
[0113] C represents the average TNF-α expression level in the negative control group;
[0114] The results showed that the inhibition rate of TNF-α expression in the positive control group was 20.94%, which is above 20%, while the result in the blank control group was 27.89%, indicating that the experiment was successful. Specific experimental results are as follows: Figure 7 .
[0115] from Figure 7As can be seen, in the three groups of inflammation tests with different concentrations of glycyrrhizin A, the inflammation inhibition rate of Example 1 was better than that of Comparative Example 1 and Comparative Example 2. Moreover, Example 1 had the highest inflammation inhibition rate at concentration 1, reaching 77.2%, while the inhibition rates of the other two groups at concentration 1 were only 45.31% (Comparative Example 2) and 23.02% (Comparative Example 1), respectively. This indicates that the mineralized collagen-encapsulated nanocrystals of Example 1 have the best inflammation inhibition effect. This test result is basically consistent with the transdermal experiment results. The glycyrrhizin nanocrystals using this encapsulation process have higher bioavailability and can better exert anti-inflammatory and soothing effects.
[0116] In addition, the inflammation suppression rate of Comparative Example 1 remained basically unchanged with the change of concentration. This may be because unencapsulated nanocrystals are easy to recrystallize and grow rapidly to reach the saturation drug concentration, so the increase in concentration does not significantly improve the inflammation suppression rate. In contrast, Comparative Example 2 uses collagen to encapsulate the drug, which enhances the sustained release of the drug. As the sample concentration increases, the anti-inflammatory effect is enhanced, but it is still significantly inferior to the effect of Example 1. This indicates that the collagen-encapsulated nanocrystals still have the problem of recrystallization, which is basically consistent with the results of the transdermal experiment.
[0117] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
[0118] The foregoing embodiments and methods described in this invention may vary based on the capabilities, experience, and preferences of those skilled in the art.
[0119] Listing the steps of the method in a certain order in this invention does not constitute any restriction on the order of the method steps.
Claims
1. A mineralized collagen-encapsulated glycyrrhizin chalcone nanocrystal, characterized in that, The mineralized material in the mineralized collagen is hydroxyapatite, the content of the mineralized collagen is 15-60 wt%, and the content of the hydroxyapatite is 1-20 wt%, based on the total weight of the mineralized collagen encapsulating glycyrrhizin nanocrystals.
2. The mineralized collagen-encapsulated glycyrrhizin chalcone nanocrystals according to claim 1, characterized in that, The collagen is animal collagen and / or recombinant collagen; Preferably, the hydroxyapatite is obtained through an in-situ mineralization reaction using a calcium ion source and a phosphate ion source; Preferably, the calcium ion source is a calcium salt, which is selected from one or more of calcium chloride, calcium nitrate, calcium carbonate and calcium citrate, and is preferably calcium chloride; Preferably, the phosphate ion source is phosphoric acid or phosphate, and the phosphate is selected from one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, potassium phosphate, calcium dihydrogen phosphate, calcium phosphate, sodium phosphate and diammonium phosphate, preferably sodium dihydrogen phosphate and disodium hydrogen phosphate.
3. A method for preparing mineralized collagen-encapsulated glycyrrhizin chalcone nanocrystals as described in claim 1 or 2, characterized in that, The preparation method includes: 1) Preparation of charge-modified glycyrrhizin chalcone nanocrystal suspension; 2) Adjust the pH of the crude suspension to 5.5-6.5 and add it to the collagen aqueous solution to form a collagen coating layer on the nanocrystals; 3) The product obtained in step 2) is mixed with calcium ion source and phosphate ion source and mineralized in situ to obtain mineralized collagen-encapsulated glycyrrhizin nanocrystals.
4. The preparation method according to claim 3, characterized in that, Step 1) includes: adding an oil phase formed by glycyrrhizin, a charge stabilizer and a good solvent to an aqueous phase formed by a non-charge stabilizer and water to obtain a charge-modified glycyrrhizin nanocrystal suspension. Preferably, the charge stabilizer is selected from one or more of oleic acid, arachidic acid, palmitic acid, stearic acid, lauric acid, myristic acid, palmitoleic acid, gallic acid, lecithin and soybean lecithin, and more preferably from one or more of arachidic acid, palmitic acid, stearic acid, lauric acid and myristic acid; Preferably, the non-charge stabilizer is selected from one or more of Tween 20, Tween 40, Tween 60, Tween 80, poloxamer 188, poloxamer 407, polyethylene glycol 200, polyethylene glycol 600, polyethylene glycol 6000, polyvinylpyrrolidone, polyvinyl alcohol, polyoxyethylene fatty alcohol ether, polyoxyethylene fatty acid ester, polyoxyethylene glycerol ester, hydroxyethyl cellulose, and hydroxypropyl methylcellulose, and more preferably from one or more of Tween 80, poloxamer 188, poloxamer 407, polyethylene glycol, polyoxyethylene fatty alcohol ether, polyoxyethylene fatty acid ester, and polyoxyethylene glycerol ester; Preferably, the good solvent is selected from one or more of methanol, ethanol, diethyl ether, isopropanol, acetonitrile, tetrahydrofuran, acetone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone, and more preferably from one or more of methanol, ethanol and isopropanol.
5. The preparation method according to claim 4, characterized in that, In step 1), the mass-volume percentage concentration of the glycyrrhizin chalcone dissolved in a good solvent is 0.1-10%, preferably 4-6%; Preferably, in step 1), the mass-volume percentage concentration of the charge stabilizer after dissolving in a good solvent is 0.01-5%, more preferably 0.05-0.2%. Preferably, in step 1), the mass-volume percentage concentration of the non-charge stabilizer after dissolving in water is 0.1-10%, more preferably 4-6%. Preferably, in step 1), the rate at which the oil phase is added to the aqueous phase is 0.1-1 mL / min, more preferably 0.3-0.4 mL / min.
6. The preparation method according to claim 3, characterized in that, In step 2), the reagent used to adjust the pH value is an acidic solution selected from one or more of formic acid, acetic acid, propionic acid, butyric acid, citric acid, oxalic acid, succinic acid, tartaric acid, and malic acid. Preferably, the collagen is derived from animal collagen and / or recombinant collagen; Preferably, in step 2), the mass ratio of the nanocrystals to collagen is 1:(0.1-1.5).
7. The preparation method according to claim 3, characterized in that, Step 3) includes: mixing the collagen-encapsulated glycyrrhizin nanocrystals obtained in step 2) with a buffer solution of calcium ion source and phosphate ion source with pH adjusted to weak alkalinity, and performing in-situ mineralization to obtain mineralized collagen-encapsulated glycyrrhizin nanocrystals. Preferably, the calcium ion source is selected from one or more of calcium chloride, calcium carbonate, calcium phosphate, calcium nitrate and calcium citrate, and is preferably calcium chloride; Preferably, the phosphate ion source is selected from one or more of phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, potassium phosphate, calcium dihydrogen phosphate, calcium phosphate, sodium phosphate and diammonium phosphate, and preferably sodium dihydrogen phosphate and disodium hydrogen phosphate. Preferably, in step 3), the molar concentration of calcium ions in the buffer solution is 0.01-0.5 mol / L, more preferably 0.03-0.2 mol / L; Preferably, in step 3), the molar concentration of phosphate ions in the buffer solution is 0.01-0.5 mol / L, more preferably 0.04-0.2 mol / L.
8. The preparation method according to claim 3, characterized in that, In step 3), the pH value of the weakly alkaline solution is 7-8; Preferably, in step 3), the reagent used to adjust the pH value is an alkaline reagent, selected from one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate, potassium bicarbonate, sodium carbonate, potassium carbonate, disodium hydrogen phosphate, and dipotassium hydrogen phosphate. Preferably, in step 3), the molar ratio of calcium ions to phosphate ions in the buffer solution is (0.5-5):1, more preferably (0.75-1.5):1; Preferably, in step 3), the temperature of the in-situ mineralization reaction is 15-40℃, and the time of the in-situ mineralization reaction is 6-72h; Preferably, the glycyrrhizin is selected from one or more of glycyrrhizin A, glycyrrhizin B, glycyrrhizin C, glycyrrhizin D and glycyrrhizin E, with glycyrrhizin A being the most preferred.
9. An emulsion composition, characterized in that, The emulsion composition comprises mineralized collagen-encapsulated glycyrrhizin nanocrystals as described in claim 1 or 2, or mineralized collagen-encapsulated glycyrrhizin nanocrystals prepared by any one of the preparation methods described in claims 3-8, an emulsifier, and a thickener; Preferably, the emulsion composition further comprises other active ingredients; Preferably, the emulsifier is selected from one or two of hydrogenated lecithin and polydimethylsiloxane; Preferably, the thickener is selected from one or more of carboxymethyl cellulose, xanthan gum, and sodium hyaluronate; Preferably, the other active ingredients are selected from one or two of carnosine and ergothioneine.
10. The application of mineralized collagen-encapsulated glycyrrhizin nanocrystals as described in claim 1 or 2, or mineralized collagen-encapsulated glycyrrhizin nanocrystals prepared by the preparation method as described in any one of claims 3-8, in the preparation of cosmetics.
Citation Information
Patent Citations
Drug-loaded hydroxyapatite and novel indocyanine green liquid fluorocarbon nanosystem
CN110115772B